15.3k views
3 votes
I need help asap please

I need help asap please-example-1
User Advanced
by
5.3k points

1 Answer

2 votes

Answer:


x = -(3)/(2) or
x = 1

Explanation:

Using the zero product property, first step is to set the given equation,
2x^2 + x - 1 = 2 , to zero. Then factorise the left side.

Thus,


2x^2 + x - 1 = 2

Subtract 2 from both sides


2x^2 + x - 1 - 2 = 2 - 2


2x^2 + x - 3 = 0

Factorise the left side


2x^2 + 3x - 2x - 3 = 0


x(2x + 3) - 1(2x + 3) = 0


(x - 1)(2x + 3) = 0

Find the solution


x - 1 = 0

Or


2x + 3 = 0


x = 1

Or


2x + 3 = 0


2x = -3


x = -(3)/(2)

The answer is:
x = 1 or
x = -(3)/(2)

User SCFrench
by
5.3k points